ANALISA KEANDALAN SISTEM TENAGA LISTRIK JAWA TENGAH DAN DIY PERIODE TAHUN 2009-2011 - Eri Yawantoro; Bambang Supradono; Achmad Solichan (PSTE UNIMUS, 2012)
Power Plant units are responsible for providing power generation in the power system so that the load can be served.Poer Plant units may trouble each time. The disorder resulting plants cannot operate. If this interference occurs at the same time on several large generating units, it is possible that the power available in the system is reduced such that the system is not sufficient to serve the load. Reliability cf the electrical system must be maintained and enhanced, so that the load needs to be served. Thus it is necessary to investigate whether or not the reliability of the system every year. Reliability of the electrical system can be determined by calculating the value of (loss of load probability) LOLP with units of days / year. The smaller the value, the better the level of LOLPkendalan an electrical system. In 2009 the electrical system of Central Java and Yogyakarta not meet the standards, ie the value of LOLP 4.088 days / year. For the years 2010 and 2011 has increased reliability and meet the standards, with the value of 0.043 days in 2010 and 0.017 in 2011 days.Keywords: LOLP, reliability of Electric Power Systems